A Comparative Study of Perceived Social Support and Depression among Elderly Members of Senior Day Centers, Elderly Residents in Nursing Homes, and Elderly Living at Home - Maryam Seddigh; Maryam Hazrati; Mozhgan Jokar; Amir Mansouri; Mohammad-Rafi Bazrafshan; Maryam Rasti; Esmaeil Kavi (Wolters Kluwer Medknow Publications, 2020)
Background: Social support perceived by the elderly can reduce mental health problems including depression. In Iranian society, some elderly people spend their elderly years in senior day care centers established to promote social protection for the elderly. Therefore, the purpose of this study was to assess perceived social support and depression in the elderly members of senior day care centers and compare the results with that of elderly individuals living at nursing homes and at home. Materials and Methods: This descriptive, cross-sectional study was conducted on 315 elderly people. The participants were selected using stratified random sampling method and a random number table. The data collection tools used consisted of a demographic characteristics questionnaire, the Barthel index for assessing Activities of Daily Living (ADL), Social Support Appraisals (SSS-As) scale, and Geriatric Depression Scale short form (GDS-15). ANOVA, Chi-square, the Pearson correlation coefficient, and linear regression analysis were used to examine the hypotheses. Results: The results showed that with increasing social support, depression decreased in all three groups, which was statistically significant in the two elderly groups living in nursing homes (r = −0.19, p = 0.044) and elderly members of senior day centers (r = −0.18, p = 0.049). Conclusions: According to the results, it can be concluded that senior day care centers have been able to promote perceived social support in the elderly through their participation in daily activities and social activities, and thus were able to reduce depression significantly compared to the other two groups.